The Effect of Potting Mix and Topsoil on The Growth Performance of Wing Bean - Fathiyah Malhoky Idrus (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To differentiate the water holding capacity of potting mix and top soil media use for winged bean plant. To evaluate the growth performance of winged bean in potting mix and top soil by plant height and number of leaf. To develop the growth curve of winged bean crop in potting mix and topsoil.